Unsportsmanlike Conduct : Exploiting College Athletes - Byers, Walter, 1922-2015 (Book collections on Project MUSE., 1995)
Byers believes that modern-day college sports are no longer a student activity: they are a high-dollar commercial enterprise, and college athletes should have the same access to the free market as their coaches and colleges. He favors no one as he cites individual cases of corruption in NCAA history. From Byers's first enforcement case, against the University of Kentucky in 1952, to the NCAA's 1987 "death penalty" levied against Southern Methodist University of Dallas, he shows the change in the athletic environment from simple rules and personally responsible officials to convoluted, cyclopedic regulations with high-priced legal firms defending college violators against a limited NCAA enforcement system. This book is a must for anyone involved in college sports - athletes, coaches, fans, college faculty, and administrators.